Optimal path planning for urban vehicles using Internet of Things: a new navigation perspective - Alawadhi, Nayef; Taha Alshaikhli, Imad Fakhri; Alkandari, Abdulrahman; Tahir, Mahnaz (American Scientific Publishers, 2019)
One of the important applications in intelligent transportationsystem is path planning for vehicles at urban areas. A driver can reach a destination in a short time with a pleasant ride using less fuel and reach his or her destination safely. However, the destination status may change, and no more becomes a desired destination. In this paper we highlighted, discussed and analyzed related works for vehicle’s path planning using Internet of Things (IoT). A new perspective for the destination was also proposed which defines how important considering the updated information of the destination in real-time using IoT that brings driver’s attention when planning for a trip. A mathematical model for an optimal path planning was introduced which composes of two cost functions; path planning function and destination function. A gas station scenario was introduced as an example to demonstrate the proposed model. Futuristic look at integration design for the proposedsystem was also highlighted.